The abundance and spatial distribution of the Eurasian рygmy owl, Glaucidium passerinum (Strigiformes, Strigidae), in Rivnenskyi Nature Reserve, Ukraine - Franchuk, M.V.; Yanenko, V.O. (Збірник праць Зоологічного музею, 2018)
The breeding status and abundance of the Eurasian pygmy owl Glaucidium passerinum (Linnaeus, 1758) in Rivnenskyi Nature Reserve was estimated based on results of field research conducted in 2013 to 2018. We suggest the nesting of 9 to 12 pairs of the Eurasian pygmy owl in the territory of the Reserve, in particular 7 to 10 pairs in Perebrody site, 1 or 2 pairs in Somyne site and a single pair in Syra Pohonia site. The Eurasian pygmy owl has diurnal activity, which facilitates the species’ identification during field studies. It was noted that the voice activity of the tawny owl (Strix aluco), the great grey owl (Strix nebulosa) and the northern goshawk (Accipiter gentilis) leads to the termination of the pygmy owl’s vocalization. Установлен современный гнездовой статус и численность воробьиного сыча, Glaucidium passerinum (Linnaeus, 1758), на территории Ровенского природного заповедника по результатам полевых исследований 2013–2018 гг. Сделано предположение о гнездовании 9–12 пар воробьиного сыча на территории массивов заповедника (7–10 пар в массиве Переброды; 1–2 пар — Сомыне, одна пара на массиве Сырая Погоня). Воробьиный сыч на территории исследования проявляет дневную активность, чем облегчает полевые работы по его идентификации. Отмечено, что на прекращение вокализации воробьиного сыча влияет активизация токования серой неясыти (Strix aluco Linnaeus, 1758), бородатой неясыти (Strix nebulosa Johann Reinhold Forster, 1772) и ястреба-тетеревятника (Accipiter gentilis Linnaeus, 1758). Встановлено сучасний гніздовий статус та чисельність сичика-горобця, Glaucidium passerinum (Linnaeus, 1758), на території Рівненського природного заповідника за результатами польових обстежень 2013–2018 рр. Припускається гніздування 9–12 пар сичика-горобця на масивах заповідника (7–10 пар на масиві Переброди; 1–2 пар — Сомине, одна пара на масиві Сира Погоня). Сичик-горобець на території дослідження проявляє денну активність, що полегшує польові роботи по його ідентифікації. Відмічено, що на припинення вокалізації сичика-горобця впливає активізація токування сови сірої (Strix aluco Linnaeus, 1758), бородатої (Strix nebulosa Johann Reinhold Forster, 1772) та яструба великого (Accipiter gentilis Linnaeus, 1758).